2018
DOI: 10.1073/pnas.1809189115
|View full text |Cite|
|
Sign up to set email alerts
|

Activity-dependent bulk endocytosis proteome reveals a key presynaptic role for the monomeric GTPase Rab11

Abstract: SignificanceThe maintenance of neurotransmission by synaptic vesicle (SV) recycling is critical to brain function. The dominant SV recycling mode during intense activity is activity-dependent bulk endocytosis (ADBE), suggesting it will perform a pivotal role in neurotransmission. However, the role of ADBE is still undetermined, due to the absence of identified molecules specific for this process. The determination of the bulk endosome proteome (a key ADBE organelle) revealed that it has a unique molecular sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 87 publications
1
58
0
Order By: Relevance
“…Calcineurin is located on bulk endosomes (Kokotos et al ) and plays a key role in SV generation from these organelles (Cheung and Cousin ). We showed that SV generation was disrupted when a competitive peptide that interferes with calcineurin interactions was applied to neurons, indicating that calcineurin must be located closely to sites of calcium efflux on bulk endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin is located on bulk endosomes (Kokotos et al ) and plays a key role in SV generation from these organelles (Cheung and Cousin ). We showed that SV generation was disrupted when a competitive peptide that interferes with calcineurin interactions was applied to neurons, indicating that calcineurin must be located closely to sites of calcium efflux on bulk endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, ADBE inhibition results in a reduced capacity to sustain neurotransmitter release in the longer term (Nicholson-Fish et al, 2015). When one considers the scope for its bidirectional modulation (Smillie et al, 2013;Kokotos et al, 2018), this suggests that ADBE provides a plastic, scalable mechanism to alter neuronal output.…”
Section: Activity-dependent Bulk Endocytosismentioning
confidence: 99%
“…Typical SV proteins (cargoes) such as VAMP2, synaptophysin, and vesicular glutamate transporter (v-Glut) are retrieved by ADBE (Nicholson-Fish et al, 2015;Kokotos et al, 2018), though it is unclear whether this retrieval is direct or due to escape of excess cargo from saturated clustering mechanisms at the periactive zone. Some cargoes, such as VAMP4, are preferentially accumulated by ADBE, perhaps explaining why VAMP4 is also essential for this mode of endocytosis (Nicholson-Fish et al, 2015).…”
Section: Activity-dependent Bulk Endocytosismentioning
confidence: 99%
“…Indeed, VAMP4 -present in CTX-M3 -is an essential molecule for activity-dependent bulk endocytosis (ADBE), 165 and several module proteins (including RAB GTPases RAB7a and RAB18) overlap with the ADBE proteome. 166 This suggests a parsimonious explanation that this module concerns the maintenance of organelles and proteins required for long-term neuronal activity, (i.e., mitostasis and ADBE proteostasis), through activity-dependent mRNA transcription and neuropil targeting. 167 CTX-M3 does show suggestive evidence of preservation outside of cortical regions (figure S6), and it may appear cortex-specific simply because it is easier to uncover neuronal biology in regions with the highest proportion of neurons, such as the cortex.…”
Section: Discussionmentioning
confidence: 99%